2011
DOI: 10.1177/0361684311410209
|View full text |Cite
|
Sign up to set email alerts
|

“It’s a Comparison Thing, Isn’t It?”

Abstract: Women's feelings about their body and their appearance are an important aspect of their lives, yet little is known about the ways in which partner relationships shape these feelings. There has been some debate about whether or not samesex relationships offer protection to nonheterosexual (lesbian and bisexual) women from potentially harmful social appearance pressures, but there has been little empirical exploration of this issue. We contribute to the debate by presenting findings from a British qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Second, past studies have indicated that bisexual women worry about their appearance and conform to ideals of femininity (e.g., thinness) more in relationships with men than women (Huxley, Clarke, & Halliwell, 2011;Taub, 1999). Thus, bisexual women in relationships with women may have greater freedom in defming their own standards of attractiveness.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Second, past studies have indicated that bisexual women worry about their appearance and conform to ideals of femininity (e.g., thinness) more in relationships with men than women (Huxley, Clarke, & Halliwell, 2011;Taub, 1999). Thus, bisexual women in relationships with women may have greater freedom in defming their own standards of attractiveness.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…However, there is relatively less research examining these issues among lesbian women and the research that is available provides conflicting information. In particular, there has been speculation that identification with lesbian culture may serve a protective function against body dissatisfaction (Huxley, Clarke, & Halliwell, 2011); however, findings examining lesbian women's vulnerability to body dissatisfaction (and related eating disorders) remain mixed. Peplau et al (2009) have reported few differences (d ¼ .07) between lesbian and heterosexual women's body dissatisfaction.…”
Section: Sexual Orientation and Body Imagementioning
confidence: 99%
“…Chmielewski and Yost (2013) found that bisexual women experience a tension between their resistance to adopt sexist ideals, characteristic of feminist women, and the assumption of the thin ideal of feminine beauty. Previous studies have reported that bisexual women worry about their body image and conform to the feminine ideal (e.g., thinness) more so in relationships with men, and may enjoy greater freedom in defining their own standards of attractiveness in same-sex relationships (Huxley et al, 2011). Research also suggests that bisexual women may have more body image issues than lesbian and heterosexual women (Boehmer et al, 2007; Polimeni et al, 2009); are more prone to developing eating disorders compared to lesbian women (Koh and Ross, 2006); and exhibit higher rates of unhealthy weight-control behaviors than heterosexual women (Polimeni et al, 2009).…”
Section: Introductionmentioning
confidence: 99%